Forest rehabilitation in Indonesia: where to after three decades? - Nawir, A.A.; Murniati; Rumboko, L. (Center for International Forestry Research, 2007)
Rehabilitation activities in Indonesia have a long-history of more than three decades, implemented in more than 400 locations. Successful projects are characterised by the active involvement of local people, and the technical intervention used tailored to address the specific ecological causes of degradation that concern local people. However, sustaining the positive impacts beyond the project time is still the biggest challenge. Rehabilitation efforts have been lagging behind the increasing rates of deforestation and land degradation. This has been largely due to the complexities of the driving factors causing the degradation, which neither projects nor have other government programmes been able to simultaneously address. Currently, there are more complex driving factors of deforestation to be dealt with, such as illegal logging and forest encroachment. Therefore, addressing the causes of deforestation and land degradation, which usually are also the continuing disturbances threatening sustainable rehabilitation activities, should be part of the project’s priorities. Designing the right economic and social incentives is important to stimulate greater community roles in rehabilitation initiatives. Project derived economic and livelihood benefits, generated from ecological improvements, tend to sustain in the long-term more than the benefits from project-based economic opportunities.